(untitled) (Journal of the College of Languages (JCL), 2018)
Abstract Theoretically, the aim of the paper is identify linguistic expressions, such as proverbs, wise sayings, and popular sayings, used by the playwright A. N. Ostrovsky , along with their translations into Arabic by the Iraqi translator Abdullah Habbah and the Syrian translator HashimHumadi. And practically, there were found about fifty sayings, made of proverbs, wise sayings and popular sayings, which were identified and taken into analysis in respect to their Arabic translation , with the specification of the best rendition of the original text. Critics and professionals emphasize, within the literary field, that literary translation requires effective employment of linguistic elements in the translated text. Thus, such employment is seen as a means of forming a mocking scene which works as a community mirror on the principle of (laughter via tears) or what is termed as black comedy. This is a means exploited by a writer to feed the receptor’s imagination with various images as is the case of the play under research.